On the determinants and effects of political influence - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2007)
This paper uses a large cross-country survey of business firms to assess their influence on government policies. It is found that influence is associated with larger, government-owned firms that have a high degree of ownership concentration. In contrast, foreign ownership matters little. It is also found that the extent to which government policies and legislation are viewed as impeding firm growth decreases with political influence and, independently, with a country's level of institutional quality.
Keywords: H00; D21; O10; 330; Politics; Institutions; Influence; Ownership; Government Policies; Firm Growth; Interessenpolitik; Betriebsgröße; Eigentümerstruktur; Wirtschaftskonzentration; Theorie; Schätzung; Welt